Bibliometric Analysis of Game Research Trends in Elementary Learning and Self-Regulated Learning Skill - Primaestri, Wening; Akhyar, Muhammad; Sutimin, Leo Agung (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
Self-regulated learning is a skill that is important to be taught to students because this skill is useful in their learning environment management to achieve the best learning outcomes. Thus, teaching this ability as early as possible is better, such as in elementary school. One alternative way to introduce and teach this skill is through games. This study aims to capture the relevant previous research landscape regarding the use of games in elementary school learning and for self-regulated learning from 2020 to 2023 using bibliometric analysis with the help of the VOSviewer application. The Scopus database was used to search for data with the keywords